Independent and Healthy through Complementary Therapy for the Elderly at Griya Asih Lawang: Mandiri dan Sehat Melalui Terapi Komplementer bagi Lansia di Griya Asih Lawang - Eny Rahmawati; Eka Yuni Indah Nurmala; Nadhifah Rahmawati (Poltekkes Kemenkes Palu, 2022)
Introduction: The achievement of healthy aging is expected to be able to improve the physical, social and mental health of the elderly so that they can play an active role in society and enjoy an independent life without discrimination. The guidance and health services for the elderly need to be improved with the aim of improving the health status and quality of life of the elderly for health and independence through complementary therapies. The purpose of this community service is to train RAAL Griya Asih caregivers and the elderly about complementary therapies. The target/partner of this activity is RAAL Griya Asih Lawang which consists of 33 elderly, 7 RAAL caregivers. The service method is the provision of health education in the form of counseling, demonstrations for each elderly about complementary therapies, namely Spiritual Emotional Freedom Technique (SEFT), back acupressure (mask) and relaxation. The evaluation method is to evaluate the ability by doing one-on-one practice and then being evaluated for the next 4 days. Result: Increased knowledge for RAAL caregivers from 28.28% who lacked knowledge to lack of knowledge and became good as much as 71.42%. The improvement of skills for RAAL caregivers, initially there were less as much as 42.86%, to less skills only 14.29% and to be good as much as 28.57% and enough by 57.14%. Increased knowledge for the elderly RAAL, initially most of the knowledge is lacking as much as 78.78% to 24.25% good and 45.45% enough. Improved skills for RAAL elderly, initially most of the skills were lacking as much as 75.76% to good at 12.12% and sufficient at 60.61%.The results of the activity are increasing the knowledge and skills of the elderly and caregivers of RAAL Griya Asih on complementary abilities, namely SEFT, masking and relaxation, because at first at RAAL Griya Asih they have not applied the three complementary techniques. Increased knowledge and skills on complementary techniques will contribute to efforts towards independence and health of the elderly.